Pengaruh Brand Ambassador, Brand Image, dan Kualitas Produk Terhadap Keputusan Pembelian Pada Pengguna Sepatu Ventela di Kecamatan Surabaya Gubeng - Afifah, Farhanah Dhia (Research Journal of Social Science and Economics, 2025)
The phenomenon of competition that dominates the business life of the sneaker industry is currently generated by many national and international shoe brand companies. From the results of the data, competition for local shoe brands and international shoe brands in the sneaker industry is very tight in 2017-2023. This study uses a quantitative method using a questionnaire in the form of google form as the instrument. The population in this study are consumers who use ventella shoes in the Gubeng District, Surabaya City. The samplingtechnique used is non-probability sampling using a purposive sampling technique, where the sample taken is 96 respondents with certain characteristics. The analysis techniques in this study were validity test, rehabilitation test, linear test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, t test, F test, and the Coefficientof Determination (R2). The results of the analysis in the Simultaneous test stated that there was a significant relationship between Brand Ambassador, Brand Image, and Product Quality which simultaneously had a significant influence on Purchase Decisions for ventella shoe usersin Surabaya gubeng sub-district.